2011
DOI: 10.1002/mc.20745
|View full text |Cite
|
Sign up to set email alerts
|

Crk and CrkL present with different expression and significance in epithelial ovarian carcinoma

Abstract: Adaptor protein Crk and CrkL were thought to be closely related because both consist of one SH2 and two SH3 domains and share 60% homology with the highest identity within their functional domains. Their functions were most presumed to be in part, if not all, redundant. And both were suggested to be implicated in carcinogenesis. In this study, both Crk and CrkL presented with much higher expression in ovarian cancer tissues than those in normal and benign ovarian tissues. However, in contrast with CrkL, high C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…CrkL can regulate apoptosis and cell proliferation in the noncardiomyocytes. [16][17][18][19] Total knockout of CrkL 20 could lead to most of the mice to die before birth because of severe heart developmental abnormalities. It reminds that CrkL participates crucial roles in the development of embryonic heart.…”
Section: Discussionmentioning
confidence: 99%
“…CrkL can regulate apoptosis and cell proliferation in the noncardiomyocytes. [16][17][18][19] Total knockout of CrkL 20 could lead to most of the mice to die before birth because of severe heart developmental abnormalities. It reminds that CrkL participates crucial roles in the development of embryonic heart.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [18] reported that both CRK and CRKL presented with higher expression in ovarian cancer tissues than those in normal and benign ovarian tissue by immunohistochemical analysis. The detailed oncogenic function of CRKL including in vivo analysis in non-hematopoietic tumors has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…CRKL commonly localizes in multiple intracellular compartments mapped at 22q11.21 encoding a protein of 36 kDa [14]. CRKL deregulation is involved in the development and progression of a variety of cancers including gastric cancer (GC), glioblastoma multiforme (GBM), hepatocellular carcinoma (HCC), bladder cancer, lung cancer, colon cancer, ovarian cancer, leukemia, breast cancer, head and neck cancer, rhabdomyosarcoma and neuroblastoma [15][16][17][18][19][20][21][22]. Nevertheless, the role and action mechanism of CRKL in tumor progression are still unclear.…”
Section: Introductionmentioning
confidence: 99%